THE USE OF FACEBOOK IN ENGLISH LANGUAGE TEACHING (ELT) TO INCREASE STUDENTS’ ABILITY TO WRITE RECOUNT TEXT: A Pre-Experimental Research - Sari, Ikmul; Sulfasyah; Andi Baso, Farisha (FKIP Unismuh Makassar, 2018)
The aim of this research was find out whether the use of Facebook Group as a medium effective to increase students’ ability in writing recount text of the second grade students of MTs Aisyiyah Sungguminasa. This research used Pre-Experimental Research. The subject of the research was the second grade students with the sample of this research was 25 students from class VIII C and it used Purposive Sampling Technique. The researcher gave recout text to measure the students writing recount text. All of the students were given pre-test before using Facebook Group as a medium and after they got the treatment, the researcher gave post test to the students. The result of this research showed that the writing recount text of the second grade students of MTs Aisyiyah Sungguminasa, before taught by using Facebook Group was poor categorized. The mean score of pre-test was 61,04 and mean score of post-test was 85,48. It means that the mean score of post-test was greater than the mean score of pre-test. Then the improvement of the students’ writing ability was 40%. Then the calculating the t-test value for recount text was 12,87 and t-table for recount text was 2.064. it mean that the t-test was greater than t-table. The alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. Based on the research findings, it could be conclude, that applying Facebook Group as a medium had significant to increase students’ ability at the second grade of MTs Aisyiyah Sungguminasa.